Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1088/0953-4075/29/2/017
|View full text |Cite
|
Sign up to set email alerts
|

Differential cross sections for radiation assisted collisions between atoms

Abstract: We report angle resolved measurements of the excited Na atoms from the process with non-resonant light. The experiment provides a method to probe the NaKr collision pair by a photon. The Na() angular distribution shows an oscillatory structure, which can be used for a test of the NaKr potential curve system. The signal depends strongly upon the polarization of the photon. The effect provides information about the geometric properties of the collision pair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Grosser et al [8] used a continuous beam of Na atoms, a pulsed beam of Kr atoms, two pulsed (pump and probe) laser beams, and crossed all beams in a small interaction volume. They explained an oscillatory structure in the angular distribution of excited Na projectiles after laser-assisted collisions with Kr atoms in terms of optical molecular transitions in the transient NaKr complex.…”
Section: · 10mentioning
confidence: 99%
“…Grosser et al [8] used a continuous beam of Na atoms, a pulsed beam of Kr atoms, two pulsed (pump and probe) laser beams, and crossed all beams in a small interaction volume. They explained an oscillatory structure in the angular distribution of excited Na projectiles after laser-assisted collisions with Kr atoms in terms of optical molecular transitions in the transient NaKr complex.…”
Section: · 10mentioning
confidence: 99%
“…The experiment has been described previously. , We therefore summarize here only the most important aspects. Figure shows the experimental setup.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We have demonstrated that crossed beam experiments on laser assisted (“optical”) atom−atom collisions, where the photon energy h ν is detuned with respect to the atomic A−A* transition energy, offer unprecedented possibilities for observing collision processes and for investigating the underlying molecular interactions. Especially, polarization experiments have been shown to give direct access to the geometric properties of the collision complex AM.…”
Section: Introductionmentioning
confidence: 99%
“…2͒ we use two atomic beams and two laser beams intersecting each other in the scattering volume. 4,5 During the optical collision process two atoms and one photon of the excitation laser interact to produce an excited Na atom at the end of the collision. The second laser transfers the excited atom to a long-lived Rydberg state, Na͑3 p ͒ 2 P 1/2,3/2 ϩhЈ˜Na͑nd͒, nϭ20, .…”
mentioning
confidence: 99%